2020
DOI: 10.1088/1742-6596/1600/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of the Deflector Angle on the Droplet Trajectory Based on the CFD Discrete Phase Model

Abstract: In order to investigate the effect of the air deflector sprayer deflector angle on the droplet drift, this paper based on the particle tracking technology of the discrete phase model of CFD, studied the characteristics of droplets at different positions of the deflector angle. In this paper, six groups of nozzles are set at the air outlet in the cuboid calculation area with the conditions of 4000mm × 2000mm × 3300mm. Under the same wind conditions, the sprayer’s deflector changes and the droplet motion charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The benefit of the CFD-based approach is that it gives comprehensive information about the local variations of flow parameters where the measurements are either difficult or impractical to conduct. In the case of a low particle concentration, choosing the CFD-DPM method can improve the calculation efficiency while ensuring calculation accuracy [10,11]. Rui Li et al [12], showed the design optimization of a hemispherical protrusion for mitigating elbow erosion via CFD-DPM.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of the CFD-based approach is that it gives comprehensive information about the local variations of flow parameters where the measurements are either difficult or impractical to conduct. In the case of a low particle concentration, choosing the CFD-DPM method can improve the calculation efficiency while ensuring calculation accuracy [10,11]. Rui Li et al [12], showed the design optimization of a hemispherical protrusion for mitigating elbow erosion via CFD-DPM.…”
Section: Introductionmentioning
confidence: 99%